Development of locating system design module for freeform workpieces in computer-aided fixture design platform. (November 2018) - Parvaz, Hadi; Nategh, Mohammad Javad
Abstract: Development of an efficient computer-aided platform for fixture design requires intelligent algorithms to be developed as decision making tools for different designing functions. Locating system design is among the representative fixture design functions which are in need of such intelligent algorithms to implement their complicated roles. This rather unmet need has already hampered the development of automated computer-aided fixture design systems. The authors have proposed an analytical and algorithmic locating system design procedure as a part of their continuous effort to establish a PythonOCC-based platform, which is the subject of the present paper. In order to surmount the geometrical restrictions, workpieces with freeform geometries of NURBS types have been taken into consideration for locating system design. Constraining workpiece's degrees of freedom, capacity of locating surfaces in bearing the machining loads, and ease of workpiece loading and unloading into and from the fixture together with some other checking rules constitute the characteristic criteria of the proposed analytic procedure. The proposed procedure has been employed for several workpieces with freeform geometries to evaluate its efficacy. Highlights: Locating system for freeform workpieces has been analyzed. Main criteria are total constraint, bearing cutting forces, easy loading/unloading. Supplementary checking rules are jamming avoidance and workpiece stability. The suggested model is implemented in a CAFD platform already developed by authors.